2017
DOI: 10.1111/epi.13907
|View full text |Cite
|
Sign up to set email alerts
|

Automated analysis of seizure semiology and brain electrical activity in presurgery evaluation of epilepsy: A focused survey

Abstract: Epilepsy being one of the most prevalent neurological disorders, affecting approximately 50 million people worldwide, and with almost 30-40% of patients experiencing partial epilepsy being nonresponsive to medication, epilepsy surgery is widely accepted as an effective therapeutic option. Presurgical evaluation has advanced significantly using noninvasive techniques based on video monitoring, neuroimaging, and electrophysiological and neuropsychological tests; however, certain clinical settings call for invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 118 publications
0
26
0
1
Order By: Relevance
“…Oro-alimentary automatisms may also occur rhythmically [3,31]. Amongst possible methods of movement quantification in neurological disorders (for comprehensive review, see [12]), there is increasing interest in video analysis techniques, including those based on deep learning or machine learning, for automated analysis of movements in epileptic seizures [1,2,7,8,33] and for motor stereotypies (e.g., in autism [20]). However, such studies have tended to focus on detection and categorization of movement patterns; quantification of multi-segmental rhythmic behaviors in terms of time-evolving movement frequencies has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Oro-alimentary automatisms may also occur rhythmically [3,31]. Amongst possible methods of movement quantification in neurological disorders (for comprehensive review, see [12]), there is increasing interest in video analysis techniques, including those based on deep learning or machine learning, for automated analysis of movements in epileptic seizures [1,2,7,8,33] and for motor stereotypies (e.g., in autism [20]). However, such studies have tended to focus on detection and categorization of movement patterns; quantification of multi-segmental rhythmic behaviors in terms of time-evolving movement frequencies has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A number of EEG signal features have been considered to represent seizures (Ahmedt-Aristizabal et al, 2017; Baldassano et al, 2017; Orosco et al, 2013; Venkataraman et al, 2014); e.g., time-frequency analysis (Anusha et al, 2012; Gao et al, 2017; Li et al, 2018), wavelet transform (Adeli et al, 2003, Adeli et al, 2007; Adeli and Ghosh-Dastidar, 2010; Ayoubian et al, 2013; Faust et al, 2015; Sharma et al, 2014; Yuan et al, 2018), and nonlinear analysis (Ghosh-Dastidar et al, 2007; Takahashi et al, 2012). The detection accuracy has also improved with advances in machine learning algorithms such as the support vector machine (Satapathy et al, 2016), logistic regression (Lam et al, 2016), and neural networks (Adeli and Ghosh-Dastidar, 2010; Ghosh-Dastidar et al, 2008; Ghosh-Dastidar and Adeli, 2007, Ghosh-Dastidar and Adeli, 2009; Juárez-Guerra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies demonstrated the efficacy of deep learning in the classification of EEG signals (AliMardani et al, 2016; Dvey-Aharon et al, 2017; Jirayucharoensak et al, 2014; Ma et al, 2015; Schirrmeister et al, 2017). Yet, the performance of seizure detection by deep learning still requires improvement (Acharya et al, 2018; Ahmedt-Aristizabal et al, 2017, 2018; Thodoroff et al, 2016) compared to the level of human performance in certain visual recognition tasks (Dodge and Karam, 2017; Esteva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the study of these signs relies heavily on clinical experience and training. Given the importance of body motion patterns in the assessment of epilepsy, prior works have demonstrated that automated analysis of semiological patterns based on computer vision can support diagnosis by standard and objective assessment methods among evaluators [3,4]. Previously, we proposed a facial semiology analysis approach to identify patients with mesial temporal lobe epilepsy (MTLE) [5], and a hierarchical multi-modal system to quantify and classify patients with MTLE and extra-temporal lobe epilepsy (ETLE) based on face, body and hand motions [6].…”
Section: Introductionmentioning
confidence: 99%